Description of Leukocytes Pangasius hypophthalmus which is Fed with Extracts of Mangrove Leaf (Rhizophora apiculata) and Maintained in The Floating Cages - Rahmadona, Zikra; Syawal, Henni; Lukistyowati, Iesje (Jurnal Perikanan dan Kelautan, 2020)
Mangrove leaves (R.apiculata) contain flavonoid compounds, terpenoids, steroids, saponins, and tannins which function as antibacterial and can improve fish health. This research was carried out in August to October 2019. This research purpose was to know the proper dose of mangrove leaf (R. apiculata) added to the feed to improve fish health as seen from total leukocytes, leukocyte differentiation, and phagocytic activity of P. hypophthalmus. The method in this research was the experimental method using the Completely Randomized Design (CRD) with one factor, four treatment levels and three times replication, so that it takes 12 units of experiments. The treatments were P0 (feed without additional extract R. apiculata), P1, P2, and P3 feed which were given extract R. apiculata at a dose of 1,5 mg/kg, 1,7 mg/kg and 1,9 mg/kg of feed. The fish used is P. hypophthalmus size 8-10 cm with a stocking density of 50 fish/m3. Feeding three times a day at 08.00, 12.00, and 17.00. Blood testing was performed three times, namely the beginning of the 1st, 30th, and 60th day of maintenance. The results showed that the addition of extract (R. apiculata) into the feed had a significant effect on total leukocytes, leukocyte differentiation, phagocytic activity, survival rate and growth of absolute weight of P. hypophthalmus. The best dose is 1,7 mg/kg of feed with total leukocytes 11,17x104 cells/mm3,  lymphocytes 84,33%, neutrophils 6,67%, monocytes 9,00%, phagocytosis activity 35,00%, survival rate 97,33%, and absolute weight growth of 38,93g.